1994
DOI: 10.1063/1.110891
|View full text |Cite
|
Sign up to set email alerts
|

Photoamperic probes in scanning tunneling microscopy

Abstract: The charge generated at the apex of a semiconductor tip upon laser irradiation is utilized in a scanning tunneling microscope. We show such arrangements can produce photoinduced tunnel currents of several hundred picoamperes, sufficient for stable STM operation and sensitive enough to detect nanowatt variations in the incident optical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…36 In the next section we will see that this situation is approached for high enough forward bias, where the junction is operated in the photovoltaic regime. 13,8 …”
Section: Spin Relaxation In Surface Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In the next section we will see that this situation is approached for high enough forward bias, where the junction is operated in the photovoltaic regime. 13,8 …”
Section: Spin Relaxation In Surface Statesmentioning
confidence: 99%
“…6,7 For the STM geometry, a number of experiments supporting the feasibility of the method have been conducted. 8,9 Theoretical descriptions of spin-polarized transport in ferromagnet/semiconductor junctions also have been given. [10][11][12] These treatments focus on the tunneling process itself, while charge flows inside the semiconductor were ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In this category we recently introduced a new technique for magnetic imaging, using photosensitive semiconductor tips in a scanning tunneling microscope ͑STM͒. 7 It has been shown that semiconductor tips can yield atomic resolution, 8,9 and that they can be used as sensitive photodetectors both in a tunneling 7,9 as well as in an atomic force microscope. 10 The detection is based on separation of photoexcited electronhole pairs by the depletion field, creating a surface photovoltage and the possibility to draw a zero-bias photocurrent.…”
Section: H W Van Kesterenmentioning
confidence: 99%
“…We extensively characterized the tips by measuring current versus voltage curves with and without illumination. 9 While scanning we carefully followed the tip behavior by monitoring the quality of the topographical images and the stability of the response R. The Pt/Co multilayer consists of a 6 Å Pt base layer and 20 pairs of 3.5 Å Co and 6 Å Pt layers evaporated on a glass substrate. 12 In Fig.…”
Section: H W Van Kesterenmentioning
confidence: 99%
“…15,16 The application of GaAs for magnetic imaging has become a hot issue with the development of cleaved GaAs tips for STM operation, under ultrahigh vacuum conditions, 17 as well as under ambient conditions. 18,19 In the latter studies, optical excitation was already included, but the spin sensitivity of GaAs tips was not yet demonstrated.…”
Section: Introductionmentioning
confidence: 99%